(untitled) (Journal of the College of Basic Education, 2022)
The ignorant preaching was prioritized at the pre-Islamic society. However, the role of preaching and Muslim preachers in the 1st century AH, has been characterized by its extent through the events of the Koran and prophetic Hadiths which are supported by the prophet’s commandments (peace be upon him). When the roles of religious and political preachers increased, due to the expanded needs of society, and most of them were pious and ascetic that had high confidence at the general public, prominent characters emerged such as: Ata IbnYasar in Hijaz, Hassan Al-Basri in Iraq, Abu Idris Al-Khulani in Sham, and WahbIbnMnbh in Yemen. This mater increased their importance at ruling elites, especially after the sedition in the Islamic State at that time. The Umayyad rulers, who continued to use preachers in the service of their political orientations, exploited their opponents away from the provisions of religion and its correct origins. Many of them have lost credibility as preachers to guide people to the satisfaction of Allah and the Prophet (peace be upon him). Most of them were obedient to serve the orientations of worldly political rulers.